The Extent of Participation of Accountants in the Stages of Dev-eloping Accounting Information Systems: Case of Libyan Airlines. - شريعة بوبكر; الساحلي فاطمة (Dirasat in Economics and Business, 2013)
The aim of this study is to know the level of participation of accountants working in Libyan Airlines Company in the development of the company's accounting information systems, including planning, analysis, design, implementation and evaluation. ence. According to this result, it can be said that the accountant whom working in this company had knowledge about the recent information of technology, however, there is no contribution to improve the current information system in the company. The only participation that they provide is in the planning and analysis, but no participation is provided in designing and evaluation. The study reached that the accounttants of the Libyan Airlines Company are knowing the importance of recent technology information. Design/Methodology/Approach: The study is based on a literature review and archival research, reinforced by a qualitative case study comprised of interviews, questionnaire. The prescriptive analysis was used for both of the primary and secondary data. Research Limitation/Implications: Findings: The study results show that accountants working in the company have all factors to know the recent technology of information by rehabilitation, practical training and accumulation of experience. According to this result, it can be said that the accountant whom working in this company had knowledge about the recent information of technology, however, there is no contribution to improve the current information system in the company. The only participation that they provide is in the planning and analysis, but no participation is provided in designing and evaluation. The study reached that the accounttants of the Libyan Airlines Company are knowing the importance of recent technology information. Research Limitation/Implications: This study focuses on one case study, which does limit its generalisability. However, it also suggests fruitful research areas in considering the importance of the knowledge of technology which have determined accounting's role in developing and planned economies. Practical Implications: By providing insights about knowledge of technology factors which have determined the use of technology information in a improve accounting information system, this study has implications for similar activities as they move towards a more globalised mode of operations which enhance the role of accounting in meeting decision-making needs. Originality/Value: According to the previous results, the study suggests to develop programmers of recent technology information by helping the educating department. Also the study advice for participation of the accountants in developing of these accounting systems.